2011
DOI: 10.1249/mss.0b013e31820c0130
|View full text |Cite
|
Sign up to set email alerts
|

Association between Physical Activity and Kidney Function

Abstract: When examining the association between physical activity, measured objectively with an accelerometer, and kidney function, total and light physical activities were found to be positively associated with kidney function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(59 citation statements)
references
References 31 publications
2
56
1
Order By: Relevance
“…Exercise has a beneficial influence on most disease conditions, including diabetes [12,13,14,15] and CKD [16,17,18,19,20,21,22,23]. Regular physical activity can lead to weight loss, improves blood sugar control, reduces vascular complications, increases well-being and reduces mortality in diabetic patients [12,13,14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exercise has a beneficial influence on most disease conditions, including diabetes [12,13,14,15] and CKD [16,17,18,19,20,21,22,23]. Regular physical activity can lead to weight loss, improves blood sugar control, reduces vascular complications, increases well-being and reduces mortality in diabetic patients [12,13,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Regular physical activity can lead to weight loss, improves blood sugar control, reduces vascular complications, increases well-being and reduces mortality in diabetic patients [12,13,14,15]. Exercise has also been reported to benefit CKD patients by preserving the estimated glomerular filtration rate (eGFR), reducing proteinuria, blood pressure and blood lipids, and improving quality of life and survival [16,17,18,19,20,21,22,23]. However, most of the previous studies of the effect of exercise in CKD were of a cross-sectional or observational nature.…”
Section: Introductionmentioning
confidence: 99%
“…Several potential causes or mechanisms, including anemia, an increase in protein catabolism, an inflammatory state, and a decrease in protein synthesis, have been proposed to contribute to decreased physical function [21]. By contrast, relatively few studies have addressed physical function in the predialysis period among patients with CKD [22].…”
Section: Discussionmentioning
confidence: 99%
“…CKD in the early stages is often asymptomatic, and awareness is low [21]. However, it has been reported that patients with CKD have impaired health-related QOL even in the early stages.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, an inactive lifestyle promotes vascular inflammation, insulin resistance, obesity and hypertension. [35][36][37][38][39] Data from two independent studies 21,22 have shown that physically active patients have an improved kidney function and a lower risk of kidney function decline than inactive patients. The results of our study showing lower rates of MAU and lower UAE in physically active patients compared to inactive patients are in accordance to these findings and implicate that the vasculo-protective mechanisms mediated by regular physical exercise might translate to a reduction in renal end-organ damage.…”
Section: Discussionmentioning
confidence: 99%